2023
DOI: 10.3390/jcm12072553
|View full text |Cite
|
Sign up to set email alerts
|

EASIX Is an Accurate and Easily Available Prognostic Score in Critically Ill Patients with Advanced Liver Disease

Abstract: Acute-on-chronic liver failure (ACLF) is associated with high mortality. Objective prognostic scores are important for treatment decisions. EASIX (Endothelial Activation and Stress Index) is a simple biomarker consisting of LDH, platelets, and creatinine, reflecting endothelial dysfunction after allogeneic stem cell transplantation. Considering endothelial dysfunction in the pathogenesis of ACLF, this study aimed to test the discriminative ability of EASIX in advanced liver disease. We retrospectively analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…An index named EASIX was primarily designed and confirmed as an effective predictor of overall survival among patients with steroid-refractory graft-versus-host disease after allogeneic stem-cell transplantation which was associated with the thrombotic microangiopathy through endothelial dysfunction [7]. Then, the prognostic value of the EASIX incorporating lactate dehydrogenase, serum creatinine and platelet was verified in many kinds of patients including lower risk myelodysplastic syndromes, multiple myeloma, COVID-19, diffuse large B-cell lymphoma, small cell lung cancer, sepsis, and critically ill patients with advanced liver disease [10][11][12][13][14][15]. Some studies showed the significant correlation between the EASIX and levels of endothelial activation markers including interleukin-18, chemokine-X-C-ligand 8, C-X-C motif chemokine ligand 9, insulin like-growth-factor-1, suppressor of tumorigenicity-2, angiopoietin-2, soluble thrombomodulin [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…An index named EASIX was primarily designed and confirmed as an effective predictor of overall survival among patients with steroid-refractory graft-versus-host disease after allogeneic stem-cell transplantation which was associated with the thrombotic microangiopathy through endothelial dysfunction [7]. Then, the prognostic value of the EASIX incorporating lactate dehydrogenase, serum creatinine and platelet was verified in many kinds of patients including lower risk myelodysplastic syndromes, multiple myeloma, COVID-19, diffuse large B-cell lymphoma, small cell lung cancer, sepsis, and critically ill patients with advanced liver disease [10][11][12][13][14][15]. Some studies showed the significant correlation between the EASIX and levels of endothelial activation markers including interleukin-18, chemokine-X-C-ligand 8, C-X-C motif chemokine ligand 9, insulin like-growth-factor-1, suppressor of tumorigenicity-2, angiopoietin-2, soluble thrombomodulin [8,9].…”
Section: Discussionmentioning
confidence: 99%